Using ICT for remote sensing, crowdsourcing, and big data to unlock the potential of agricultural data - Woodard, Josh; Andriessen, Mechteld; Cohen, Courtney; Cox, Cindy M.; Fritz, Steffen; Johnson, Drew; Koo, Jawoo; McLean, Morven; See, Linda; Speck, Tara; Sturn, Tobias (World Bank, 2017)
By 2050, the global population is projected to reach approximately 9 billion. Population growth will be concentrated in poorer countries, particularly the low-income countries of Sub-Saharan Africa. By some estimates, agricultural productivity will need to double to meet everyone’s needs for food (Foley 2014). For instance, if current trends continue, yields of the world’s foremost food crops—maize, rice, wheat, and soybeans, which supply roughly two-thirds of calories consumed globally—appear likely to grow significantly more slowly than required to meet the projected global demand in 2050 (Ray et al. 2013). Some productivity growth will come from using more of the world’s arable land for agriculture, but most of the available arable land is unevenly distributed, and about half of it is found in only seven countries.